THE SAGAN-NUR: A NEW LOCALITY OF THE LATE PLIOCENE AND NEOPLEISTOCENE BIOTA IN THE WESTERN TRANSBAIKAL REGION - Kalmykov N.P.; Budaev R.Ts.; Savinov V.V. (My University, 2004)
At stripping conducted at coal deposit Sagan-Nur, in the basement of old-frozen rocks overlaying the coal tar productive layer the sediments of slopewash genesis were found. Palynological spectra confirmed the tendency in Western Transbaikalia flora changing during Pliocene-Quaternary period from boreal spruce forests with considerable admixture of broad-leaved to light coniferous forests. The analysis results for Sagan-Nur biota and geologic peculiarities enabled to recover not only chiatus in biocenotic coat evolution but also the missing member in Tugnuisk basin history on the stage of its erosion development after durable Mesozoic accumulation period.
Keywords: Pleistocene; Pliocene; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Неоген::Плиоцен